Implementasi Kaidah "Al-Yaqīnu Lā Yuzālu bi al-Syak" dalam Perspektif Fikih Keluarga - Rima Rahmayani Tanjung; Muhammad Amar Adly; Heri Firmansyah (Tabayyanu : Journal Of Islamic Law, 2025)
This article examined the application of the Islamic legal maxim al-yaqīnu lā yuzālu bi al-syak (“certainty is not overruled by doubt”) within the framework of family law. It analyzed how this principle has been interpreted and applied in resolving legal issues such as divorce (ṭalāq), maintenance (nafaqah), and legal certainty in marital relationships. Employing a qualitative, descriptive-analytical method, the study drew upon both classical Islamic jurisprudential sources—such as those authored by al-Qarāfī, al-Suyūṭī, and al-Nawawī—and contemporary legal scholarship. The analysis was grounded in the methodology of qawāʿid fiqhiyyah (Islamic legal maxims), supported by textual sources (the Qur’an and Hadith), consensus (ijmāʿ), and rational arguments. The findings demonstrated that the maxim plays a pivotal role in maintaining legal stability by ensuring that established certainties are not invalidated by subsequent doubts. Moreover, the study identified several exceptions to the maxim's applicability, particularly in ambiguous or multi-interpretable cases, revealing the principle's flexibility and relevance in modern legal contexts.